The Role of comparative religion curricula in intra-inter civilizational dialogue - Ibrahim, Haslina (ROUTLEDGE, 2013)
Comparative Religion is seen as an important curricula because it could serve as a mechanism for enhancing cross-cultural religious communication. The authors seek to examine the role of Comparative Religion as an important science for enhancing dialogue skills. Such a communication skill, however, must be developed from both intra- and inter-civilizational levels. The authors have employed an historical and textual analysis to re-examine Comparative Religion and its methodology. The authors proposed new curricula in Comparative Religion studies including criticism of the methodologies used in Comparative Religion. This includes a new methodology that considers the existing multicultural religious phenomenon as well as post–September 11, 2001 developments and the plans for departmentalization of Comparative Religion. For further benefit toward peace, harmony, and accepting co-existence, this study also highlights suggestions for developing the undergraduate and postgraduate programs at the higher education level.